Analisis Kontrastif Tindak Tutur Meminta Maaf Dalam Bahasa Jepang Dan Bahasa Sunda - Nuria Haristiani; Asti Sopiyanti (Faculty of Humanities, Universitas Jenderal Soedirman, 2019)
In everyday life when someone did a wrong doing, that someone usually performs apologyspeech act to show his/her responsibilityor remorse. However,apology speech act may be conducted using different strategies influenced by several factors, such as cultural background, social values, social statutes, gender, or even the depth of the remorse felt by the wrong doer. This study aims to determine the level of awareness of apology by Japanese Native Speakers (JNS) and Sundanese Native Speakers (SNS) in an apology situation. Apology speech act strategies used in the same situation to five interlocutors namely 1) Distant lecturer (DT), 2) Closelecturer (DA), 3) Distant senior (KT), 4) Close senior (KA), and 5) Friend (T) were also examined. A Likert scale questionnaire was used to find out about the level of awareness of apology, while Discourse Completion Test (DCT) was conducted to examine about apology speech act strategies used by seventy four (74) JNS and seventy eight (78) SNS participated in the data collection of this study. From the results, the awareness of apology between JNS and SNS both different according to the interlocutors. While in apology strategies used, both JNS and SNS mainly used the expression of apology, acknowledgment of responsibility and offer of compensation. However, there is one striking difference strategy in apologizing between JNS and SNS. SNS frequently used address terms while JNS barely used address terms to their interlocutors.